Serum antibodies to Escherichia coli serotype O157:H7 in patients with hemolytic uremic syndrome. - Chart, H (1989)
Sera from 13 patients with hemolytic uremic syndrome (HUS) and 8 healthy control subjects were examined for antibodies specific for bacterial antigens of Eschericia coli serotype O157:H7. Bacterial components, including outer membrane proteins (OMPs), lipopolysaccharide (LPS), and flagella, were reacted with sera by sodium dodecyl sulfate-polyacrylamide gel electrophoresis followed by immunoblotting and by enzyme-linked immunosorbent assay. All 13 serum samples from HUS patients contained high-titered antibodies of the immunoglobulin M class against O157 LPS and some OMPs. These same sera reacted weakly with some of the major OMPs, but not the LPS, of non-O157 strains of E. coli. Sera from patients did not contain antibodies to non-O157 LPS or H7 flagella. The possibility of using E. coli serotype O157 LPS in an enzyme-linked immunosorbent assay for the routine diagnostic testing of sera from HUS patients for evidence of O157:H7 infection is discussed.